Environmental awareness in university students and the affecting factors - Tekin, Cigdem; Gunes, Gulsen (International Journal Of Community Medicine And Public Health, 2018)
Background: The disruption of the ecological system and the environmental destructions require that we review our relations with the outer world and therefore increase our awareness on environmental problems as individuals. This study has been conducted to determine the environmental awareness levels of the first and fourth grade university students studying at different academic fields, and investigate the factors that affect the awareness levels of them. Methods: The study was designed in the descriptive style and was applied to first and fourth grade 384 students studying at various faculties of Inonu University in 2015-2016 academic years. The “Environmental Attitude Scale” was used in data collection. Results: The environmental attitude points of the first grade students were found to be 101.33±12.28, and those of the fourth graders were found to be 98.30±14.54 (p<0.05). The average point of the students who studied at Faculty of Economics and Administrative Sciences was 111.10±11.61, and those who studied at Engineering Faculty was 104.73±12.81, and was found to be higher than the other faculties(p<0.05). Conclusions: The environmental attitudes of the first grade students and the students who studied at Faculty of Economics and Administrative Sciences and Engineering Faculty were found to be higher; and the attitudes of the students who studied at Faculty of Dentistry were found to be lower. The educational status of the parents of the students, their living area in which they lived most of the time and their status of having hobbies are the other factors that influence the average points.